Carbon xerogels as electrochemical supercapacitors. Relation between impedance physicochemical parameters and electrochemical behaviour - Fernández, Pablo Sebastián (2012)
The electrochemical behavior of carbon xerogels was studied with the aim of analyzing the performance of the materials used as electrochemical supercapacitors (SC) and to relate with physicochemical parameters. These materials have areas involving 1500e2000 m2/g measured with the BET equation and a range of pore size distributions. Conventional electrochemical techniques were used as cyclic voltammetry (CV), which allowed electrochemical characterization of different materials, and chronopotentiometry (CD), in order to determine the charge storage capacity of the xerogel at different currents or discharge rates. Experimental results using electrochemical impedance spectroscopy (EIS) were interpreted with a physicochemical model that permitted identifying different parameters of the electrode, which explain the differences in the behavior of materials.